Motherhood in Film Narratives of the End of the World: Patriarchy, Neoliberalism and Struggles for Reproduction - Carmenati González, Meysis; Rubira-García, Rainer; Venet-Gutiérrez, Jacqueline (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This analysis deals with a representative referent of the neoliberal discourse: the narratives of the end of the world. We intend to verify what values and archetypes of neoliberalism are exposed in these narratives and through what discursive strategies this rationality is installed, understood as a struggle for reproduction. To this end, four contemporary fictions that address these narratives as a film genre through the mother as a character are studied. We conclude that these film narratives reinforce the traditional conception of motherhood as mandate and that maternal representations naturalizing a sexual and reproductive policy articulated to the neoliberal project predominate.